The effects of different types of social support on depressive symptomatology of prison officers - Lambert, Eric G. (Criminal justice studies, 2023)
Correctional officers are a valuable and expensive resource for prisons. Working as a correctional officer is a unique experience; it involves controlling incarcerated individuals, and this results in demands that can wear on officers, increasing chances of suffering depression. Social support has been postulated to help buffer the negative effects of working in a prison and reduce depressive symptomatology. Using data from 501 correctional officers employed in a Southern prison system, this study examined the relationship between the three types of social support – family, coworker, and supervisor – on depression symptoms measured using the Center for Epidemiologic Studies Depression (CESD) scale. Ordinary Least Squares (OLS) regression results indicated both family support and supervisor support were significantly related to the level of depression symptoms; coworker support, however, had a nonsignificant association. The results indicate efforts should be made to raise family support and supervisor support.